Daphnetin Ameliorates Neuropathic Pain via Regulation of Microglial Responses and Glycerophospholipid Metabolism in the Spinal Cord - Wulin Liang; Tianrui Zhang; Mingqian Zhang; Jiahui Gao; Rikang Huang; Xiyan Huang; Jianhua Chen; Lu Cheng; Liyuan Zhang; Zhishan Huang; Qiling Tan; Zhanhong Jia; et al. (MDPI AG, 2024)
Neuropathic pain (NP) is a common type of chronic pain caused by a lesion or disease of the somatosensory nervous system. This condition imposes a considerable economic burden on society and patients. Daphnetin (DAP) is a natural product isolated from a Chinese medicinal herb with various pharmacological activities, such as anti-inflammatory and analgesic properties. However, the underlying mechanisms of these effects are not fully understood. In the present study, we aimed to investigate DAP's anti-inflammatory and analgesic effects and explore the underlying mechanisms of action. The NP model was established as chronic constrictive injury (CCI) of the sciatic nerve, and pain sensitivity was evaluated by measuring the mechanical withdrawal threshold (MWT) and thermal withdrawal threshold (TWT). The activation of microglia in the spinal dorsal horn was measured via immunofluorescence staining. Protein levels were measured using a western blot assay. Using a mass-spectrometry proteomics platform and an LC-MS/MS-based metabolomics platform, proteins and metabolites in spinal cord tissues were extracted and analyzed. DAP treatment ameliorated the MWT and TWT in CCI rats. The expression of IL-1β, IL-6, and TNF-α was inhibited by DAP treatment in the spinal cords of CCI rats. Moreover, the activation of microglia was suppressed after DAP treatment. The elevation in the levels of P2X4, IRF8, IRF5, BDNF, and p-P38/P38 in the spinal cord caused by CCI was inhibited by DAP. Proteomics and metabolomics results indicated that DAP ameliorated the imbalance of glycerophospholipid metabolism in the spinal cords of CCI rats. DAP can potentially ameliorate NP by regulating microglial responses and glycerophospholipid metabolism in the CCI model. This study provides a pharmacological justification for using DAP in the management of NP.